PENGUATAN KAPASITAS DIGITAL MARKETING PELAKU UMKM KELURAHAN GAJAHMUNGKUR - Rahman, Faisal Riza; Wahyuningsih, Panca; Adhi, Daniel Kartika; Utama, Ari Kusuma Budi; Setyoningsih, Sari; Anjani, Sefiana (Fokus ABDIMAS, 2025)
The digital economy era demands that micro, small, and medium enterprises (MSMEs) adopt digital marketing strategies to enhance their competitiveness and sustainability. However, limited digital literacy and the absence of formal business legality remain key barriers for many MSMEs. This community empowerment program aimed to strengthen the digital capabilities of MSMEs in Gajahmungkur District, Semarang City. The intervention consisted of facilitating business registration through the issuance of Business Identification Numbers (NIB), assisting in the development and optimization of Google My Business (GMB) profiles, and providing basic branding support through logo and promotional material design. The program was implemented through a series of participatory workshops, individualized mentoring, and technical assistance. The results revealed an improvement in participants’ awareness and ability to utilize digital platforms to promote their businesses. Additionally, the formalization of business legality through NIB registration increased the trust and market access of MSMEs. This program demonstrates that integrating digital marketing assistance with legal empowerment initiatives can significantly contribute to the competitiveness and resilience of MSMEs in the evolving digital landscape. Future efforts should focus on continuous support and the expansion of digital literacy programs to ensure sustainable impact.Keywords:   Digital marketing , MSMEs, Business Registration, Google My Business, Community Empowerment